P080 State-dependency of nocturnal swallowing in healthy adults: Incidence, motor function and coordination with breathing. (9th November 2022) - Monroe, M; Carter, S; Eckert, D; Wallace, E; Bilston, L; Hudson, A; Butler, J; Gandevia, S; Kerr, G; Burke, P
Abstract: Introduction: Swallowing involves a complex motor pattern and coordination with breathing and other oro-motor behaviors. Sleep has major depressive effect on many of the motor neuronal pools that facilitate swallowing, particularly upper airway muscles. This study examines the state-depedence of the swallow motor program and coordination with breathing. Methods: Adult subjects recruited from community undertook an overnight sleep laboratory study. Subjects were instrumented to monitor sleep (EEG), breathing (nasal mask, pneumotach), swallowing / airway valving events (epiglottic pressure, submental EMG) and pharyngeal muscle activity (peroral genioglosuss EMG electrodes).We report preliminary findings (N=5; 2 female; age: 23-57 yrs) from an ongoing study. Data reported mean ± SD. Results: Nocturnal swallowing occurred intermittently thoughout the night, the majority triggered during an arousal from sleep (43-98% of all nocturnal swallows). Pharyngeal swallowing pressure was 147±44 cmH2O during quiet wake, 137±25 cmH2O during arousal from sleep, and 78 ± 23 cmH2O in stable sleep (p=0.02, RM-ANOVA). Swallows generated a brief, near-maximal burst of genioglossus EMG activity during quiet wake (90 ± 2 %, N=2) and during arousal from sleep (107 ± 24 %). In stable sleep, swallow EMG activity was 34 ± 1 %. Swallows during wakefulness occurred during expiration, the vast majority bracketed by expiration (Ex/Ex). Swallows in sleep, or during arousal from sleep, occurred in all phases of the respiratory cycle. Conclusions: Swallows elicited during arousal from sleep generate ballistic EMG and pharyngeal pressures equivalent to wake state. In contrast, swallowing in stable sleep produces a markedly attenuated EMG and pharyngeal pressure.